A comparative study of interval cholecystectomy and early cholecystectomy in acute cholecystitis - Singh, Gursimranjit; Singh, Rana Ranjit; Bansal, Darpan (International Surgery Journal, 2020)
Background: In the whole world including India, the incidence of acute cholecystitis is increasing day by day. Gall stones are the most common cause of acute cholecystitis in 90-95% of the cases. The management of acute cholecystitis was conservative earlier but now there are studies recommending early surgery as the treatment of choice. Methods: Our study was conducted on 60 patients divided into two groups of 30 each to compare the results of early surgery with the delayed surgery. Results: The overall post-operative complication rate was same in both the groups but there was significant difference in the total hospital stay and total cost of the therapy in both the groups. The average total hospital stay in early group was 6.50±4.44 days and in delayed group was 10.80±5.55 days without including the number of days in non-operating admission. Conclusions: So, early cholecystectomy was found to be more economical with less total hospital stay and less total cost of the therapy than interval cholecystectomy in acute cholecystitis.